Selection of the best thermal massage treatment for diabetes by using fuzzy analytical hierarchy process / Norpah Mahat and Syafiah Ahmad - Mahat, Norpah; Ahmah, Syafiah (UiTM Cawangan Perlis, 2017)
Diabetes is a condition in which the human blood glucose (sugar) level is abnormally high due to the lack of insulin produced by the pancreas. As diabetes has been claimed to be a disease that is incurable, researchers have come out with numerous alternatives in making it curable and one of them is thermal massage treatment. This treatment refers to the application of chiropractic where it focuses on realigning the spine where diabetes is claimed to be related to the misalignment of thoracic 7 (T7). The objective of this study is to identify and select the best and most effective thermal massage treatment session(s) required for both T1D and T2D patients of different high glucose level in the blood to be reduced to the normal glucose level by using thermal massager. This study is conducted for the diabetic patients who receive treatments from Ceragem Healthcare Centre on how to optimise their thermal massage treatments to normalise their glucose level. Fuzzy Analytical Hierarchy Process (AHP) is utilised in t his type of selection problem mainly due to the reliable results produced for the imprecise and uncertain preferences of the users in which able to be expressed as a fuzzy set (triangular fuzzy number). The findings indicated that the most significant criteria for effective thermal massage is determined by the "number of treatment session (per day)" where the best thermal massage treatment is derived from the normalised fuzzy weight of both criteria and sub - criteria.